1972
DOI: 10.1136/bmj.1.5800.617
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Abdominal Paracentesis

Abstract: We have been fortunate in our group that the executive committee has elected the medical superintendent as chairman of the executive committee. He has in the past spent a large amount of time on administration, so this position did not require him to radically alter his timetable. Nevertheless, in groups where the chairman does not already spend a large part of his time on administrative duties he must get considerable support from his colleagues within his specialty. But any clinician must be able to act as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This would apply especially to comatose patients or patients on respirators [8]. There are reports of the usefulness of DPL in postoperative cases [6,7,10,13,14] where the diagnosis of intraab dominal sepsis, bleeding or anastomotic leakage is particularly difficult because of the presence of a fresh abdominal wound and slurred responses because of analgesia. It has been suggested that DPL might be use ful in excluding surgical disease in patients thought to be presenting with 'medical' acute abdomens such as occur in porphyria, dia betic ketoacidosis and the serositis of acute rheumatic fever [4,15,16].…”
Section: Indicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…This would apply especially to comatose patients or patients on respirators [8]. There are reports of the usefulness of DPL in postoperative cases [6,7,10,13,14] where the diagnosis of intraab dominal sepsis, bleeding or anastomotic leakage is particularly difficult because of the presence of a fresh abdominal wound and slurred responses because of analgesia. It has been suggested that DPL might be use ful in excluding surgical disease in patients thought to be presenting with 'medical' acute abdomens such as occur in porphyria, dia betic ketoacidosis and the serositis of acute rheumatic fever [4,15,16].…”
Section: Indicationsmentioning
confidence: 99%
“…It has been suggested that DPL might be use ful in excluding surgical disease in patients thought to be presenting with 'medical' acute abdomens such as occur in porphyria, dia betic ketoacidosis and the serositis of acute rheumatic fever [4,15,16]. Some surgeons have even used a positive DPL result to help choose the site of the laparotomy incision for example when the DPL suggested a perfo rated appendix rather than a perforated pep tic ulcer [10,17], Even a 'normal' patient, that is one not fitting one of the above cate gories, may present a diagnostic dilemma because of an atypical history and/or equivo cal or changing abdominal signs [9,14], A patient may have severe abdominal pain in the absence of convincing abdominal signs which may reflect a whole range of diseases from spastic colon to mesenteric infarction. In the author's experience [9] the most com mon indication for DPL is the elderly, senile patient with a vague or unreliable history, fever and leucocytosis and confusing, vary ing and equivocal abdominal signs.…”
Section: Indicationsmentioning
confidence: 99%
See 3 more Smart Citations